Development of L-PLA based Intrascleral Implant for Sustained Intraocular Delivery of Dexamethasone Sodium Phosphate - Zaman, Nazia; Talukder, Md Mesbah Uddin; Haque, Tasnuva; Alam, Md Khairul; Fatema, Kanij (Stamford Journal of Pharmaceutical Sciences, 2010)
The present study was carried out to develop biodegradable intrascleral implants of Dexamethasone Sodium Phosphate and to evaluate the release pattern of the drug from the prepared implants. Intrascleral implants were prepared by using biodegradable polymer L-PLA (m.wt. 61,200 Da). Sodium chloride (NaCl), gelatin and glycerol monostearate (GMS) were used in various formulations to observe the effects of these additives on the release of Dexamethasone Sodium Phosphate from the prepared L-PLA based intrascleral implants. Five different formulations were prepared for this study and were coded as FD-1 (10%drug+L-PLA), FD-2 (20%drug+L-PLA), FD-3 (10%drug+L-PLA+5%NaCl), FD-4 (10%drug+L-PLA +5%Gelatin) and FD-5 (10%drug+L-PLA+10% GMS). Discs were prepared and made into appropriate shape before submerging into the buffer solution of pH 7.4 in different vials. The in vitro release profile of Dexamethasone Sodium Phosphate from the implants showed a biphasic release pattern with an initial burst followed by a diffusive phase. It was observed that FD-1 and FD-2 showed 19.63% and 29.87% release on the first day and 24.22% and 38.5% release respectively at day 30. The drug loading of FD-1 and FD-2 was 10% and 20% respectively. Among FD-3, FD-4 and FD-5; FD-3 showed highest release (32.1%) at day 30 in which 5% NaCl was used. FD-4 showed 27.45% release at day 30 where gelatin, a hydrophilic agent was used and FD-5 containing GMS, a lipid material, was found to be most retarding (19.22% at day 30). The results of the dissolution study provide an idea that L-PLA may be successfully used for the preparation of biodegradable intrascleral implant of Dexamethasone Sodium Phosphate. Key words: Dexamethasone Sodium Phosphate; Bioidegradable polymer; Intrascleral implants. DOI: 10.3329/sjps.v2i1.5817 Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 56-60